(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Strategy for Asparagus Sustainable One Village One Product (OVOP) Program Development in Pelaga Village, Badung Regency, Bali. Asparagus One Village One Product (OVOP) Program in Pelaga Village is one of the pilot projects in sustainable agricultural development in the Badung Regency. This program is a program of developing one main product of an area by utilizing local resources. The development of this program was quite rapid at its inception, but in recent years the asparagus OVOP program has experienced a decline in terms of production. This study aims to arrange an appropriate strategy for the sustainability of the asparagus OVOP program Pelaga Village. The data were collected through in-depth interviews and structured interviews to provide scores to the strategies that have been determined through a SWOT analysis, which then will be re-analyzed with QSPM analysis to rank the strategies that become priority strategies in the development of the asparagus OVOP program.Based on the result of the study, the OVOP program has strengths that can be utilized towards sustainable programs such as adequate facilities and infrastructure for the cultivation of asparagus and agro-climate, which support the commodity of asparagus. The priority strategy that has the highest attractiveness is a strategy of expanding local market share to dominate the asparagus market in Bali with a score of 6.15. Evaluating the strategy by taking into account the internal and external circumstances of the program from time to time needs to be considered to realize a sustainable asparagus OVOP program.